STUDIES ON A STAR CLUSTERS THE OPEN CLUSTER T9 - PISMIS, P (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1969)
Photographic photometry in UBV, calibrated with standards determined photoelectrically, is performed on stars in the region of the open cluster T9. The color-magnitude and color-color diagrams are presented. The latter diagram shows that the interstellar
BOL OBS TONAN TACUB
Keywords: STUDIES, STAR CLUSTERS, OPEN CLUSTER; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS